2022
DOI: 10.1021/acs.jpcc.2c03836
|View full text |Cite
|
Sign up to set email alerts
|

Tip-Enhanced Raman Imaging of Photocatalytic Processes at the Nanoscale

Abstract: Over the past decade, tip-enhanced Raman spectroscopy (TERS), an emerging analytical technique that provides single-molecule sensitivity and subnanometer spatial resolution, was broadly utilized to investigate fundamental physics of plasmon-driven catalysis, as well as to examine photocatalytic properties on mono and bimetallic nanostructures. In TERS, coherent oscillations of conductive electrons, which are also known as localized surface plasmon resonances (LSPRs), are induced by light at the apex of metaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…[1][2][3] LSPRs generate strongly enhanced electromagnetic fields near the NP surface that enhance scattering signals and have been used to spectroscopically track chemical reactions occurring on surfaces. 4,5 Furthermore, the decay of LSPRs gen-erates a sequence of energetic products, from excited charge carriers [6][7][8] to, eventually, localized heat. [9][10][11] Numerous studies demonstrated that both these plasmon decay products are capable of activating chemical transformations by providing energy to molecules adsorbed on the NP's surface.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] LSPRs generate strongly enhanced electromagnetic fields near the NP surface that enhance scattering signals and have been used to spectroscopically track chemical reactions occurring on surfaces. 4,5 Furthermore, the decay of LSPRs gen-erates a sequence of energetic products, from excited charge carriers [6][7][8] to, eventually, localized heat. [9][10][11] Numerous studies demonstrated that both these plasmon decay products are capable of activating chemical transformations by providing energy to molecules adsorbed on the NP's surface.…”
Section: Introductionmentioning
confidence: 99%
“…An exciting class of such probes is the one with the chemical changes triggered by the plasmonic structure itself via the photocatalytic mechanism: a novel and not fully understood process yet [27]. The mechanism behind plasmonic photocatalysis is a subject of intense debate on the role of charge transfer, photothermal effect, or their combination in the fundamentals [28][29][30]. Most photocatalytic reactions depend on the chemical environment, such as solvent [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…In the ever-expanding family of plasmon-driven photoreactions, the reductive coupling of para -nitrothiophenol (pNTP) has become a model reaction ideal for detailed mechanistic studies of plasmon-mediated surface chemistry. Plasmon-enhanced Raman spectroscopies, including both surface-enhanced Raman scattering (SERS) and tip-enhanced Raman scattering (TERS), have been utilized as surface-sensitive spectroscopic tools to precisely characterize the detailed structural evolution of molecular adsorbates during plasmon-driven photocatalytic reactions. As revealed by SERS- and TERS-based spectroscopic studies, chemisorbed pNTP molecules undergo plasmon-driven reductive coupling reactions to produce p , p ′-dimercaptoazobenzene (DMAB) on the surfaces of a diverse range of metallic nanostructures, , providing a paradigm-shifting strategy for synthesizing aromatic azo compounds. However, the kinetic features and reaction pathways vary substantially from case to case, depending sensitively on the intrinsic properties of the metallic nanocatalysts (materials compositions, plasmon resonance frequencies, local-field enhancements, and surface structures), the photoexcitation conditions (excitation wavelength, excitation power density, and light illumination geometry), and the local environment in which the reactions occur (local temperature, pH, and presence of charge carrier acceptors).…”
Section: Introductionmentioning
confidence: 99%
“…While the thiolated molecules represent so far the most intensively studied chemisorbates on metal surfaces, organic molecules may also use other nonthiolated surface-anchoring groups, such as diazonium, terminal alkyne, N -heterocyclic carbene, and isocyano groups, to form covalent interactions with metallic substrates. Previous studies of plasmon-driven nitro-coupling reactions, however, have been exclusively focusing on thiolated nitrophenyl adsorbates. , How the nonthiolated nitrophenyl derivatives behave differently from their thiolated counterparts during the plasmon-driven coupling reactions remains unexplored yet. Here we systematically compare the plasmonic reactivity and transforming kinetics of pNTP, para -nitrophenylacetylene (pNPA), and para -nitrophenylisocyanide (pNPI), which chemisorb to Ag nanoparticle surfaces using the thiol, ethynyl, and isocyano groups, respectively.…”
Section: Introductionmentioning
confidence: 99%